SPEECH FUNCTIONS OF TEACHER TALK IN CLASSROOM INTERACTION IN POLITEKNIK HARAPAN BERSAMA TEGAL - Rindang Arumdani; Utami Rosalina (Educational Tracker, 2022)
Interactions in the college non-English major are supposed to be different from the college with English major. The teacher might use bilingual (Bahasa Indonesia and English) for the whole interactions with the purpose that the students can understand what the teacher said. This study was conducted to explain the application of Sinclair and Coulthard’s IRF model which occured in teacher talk in classroom interaction. A case study was applied in this study which had been conducted at the second semester of computer program in Politeknik Harapan Bersama Tegal. The result of the study showed that the interaction in the classroom is dominated by teachers. This domination is mostly influenced by social status of the interaction participants. It can be also concluded that the interpersonal relationships between teachers and students in a classroom are more influenced by the power dimension. Meanwhile, contact and emotion dimension do not give significant impact toward the process of interaction between teachers and students in classroom. It can be interpreted that as the authoritative persons who have more access in knowledge and education (expertise), teachers keep maintaining their status by showing their domination in the interaction process.